Predictors of resilience among Iranian graduate students in University Putra Malaysia - Sabouripour, Fatemeh; Che Hassan, Norlizah; Roslan, Samsilah (Human Resource Management Academic Research Society, 2017)
This study has two main objectives, first to investigate the relationship between dimensions of social support, optimism, self-efficacy and dimensions of psychological well-being and level of resilience among Iranian graduate students in University Putra Malaysia and second, to investigate the extent to which dimensions of social support, optimism, self-efficacy and dimensions of psychological well-being significantly predict the level of resilience among Iranian graduate students in University Putra Malaysia. This research is a descriptive correlational study. The 251 of Iranian graduate students of university Putra Malaysia participated in this research. Simple random sampling was employed to collect data. According to the findings, there are positive relationships between optimism, three dimensions of social support (support from family, significant others and friends), self-efficacy, and four dimensions of psychological well-being (personal growth, purpose in life, positive relation with others and autonomy) and resilience. Also, the result of stepwise regression analysis revealed that self-efficacy, personal growth, optimism, and purpose in life are significant predictors of resilience. This study provides useful implication for the involved parties, such as Ministry of Education Malaysia, educators, counsellors, psychologist, and researchers to improve students’ resilience.